Reduction of mNAT1/hNAT2 contributes to cerebral endothelial necroptosis and Aβ accumulation in alzheimer's disease - Zou, Chengyu (2021)
The contribution and mechanism of cerebrovascular pathology in Alzheimer's disease (AD) pathogenesis are still unclear. Here, we show that venular and capillary cerebral endothelial cells (ECs) are selectively vulnerable to necroptosis in AD. We identify reduced cerebromicrovascular expression of murine N-acetyltransferase 1 (mNat1) in two AD mouse models and hNat2, the human ortholog of mNat1 and a genetic risk factor for type-2 diabetes and insulin resistance, in human AD. mNat1 deficiency in Nat1-/- mice and two AD mouse models promotes blood-brain barrier (BBB) damage and endothelial necroptosis. Decreased mNat1 expression induces lysosomal degradation of A20, an important regulator of necroptosis, and LRP1β, a key component of LRP1 complex that exports Aβ in cerebral ECs. Selective restoration of cerebral EC expression of mNAT1 delivered by adeno-associated virus (AAV) rescues cerebromicrovascular levels of A20 and LRP1β, inhibits endothelial necroptosis and activation, ameliorates mitochondrial fragmentation, reduces Aβ deposits, and improves cognitive function in the AD mouse model.